TO THE QUESTION OF IMPROVING MECHANISMS OF TARGETED TRAINING OF MEDICAL STUDENTS - O. А. Doshchannikova; Yu. N. Philippov; E. S. Bogomolova; А. L. Hlapov (Высшее образование в России)
The article addresses the problem of improvement mechanisms of training at medical university on the conditions of the target admission. The authors analyze the current state of regulatory framework regarding target teaching aspects, explore the dynamics of target admission quota. The comparison was made of entrance score of target group students and the general competition depending on the faculty. The paper traces the learning trajectory of the students of targeted training. Special attention is paid to the frequency and structure of reasons for targeted training students’ dismissal form the university. The authors have analyzed the agreements on target training as well as measures for socio-economic support of this group of students. In conclusion the paper formulates suggestions for improving the target training of medical personnel.